A comparison of modern investment-linked pension savings products. (3rd November 2014) - Linnemann, Per; Bruhn, Kenneth; Steffensen, Mogens
Abstract This paper is a continuation of and a supplement to the paper by Jørgensen & Linnemann. Both papers deal with TimePension – a (formula-based) smoothed investment-linked annuity pension scheme. Both papers compare TimePension with other pension savings products using stochastic financial simulation. TimePension as well as the financial model and simulation concept being used in both papers were introduced in the paper op cit. Jørgensen & Linnemann compare TimePension with a traditional with-profits scheme involving bonus entitlement and an investment-linked Unit Link scheme with a fixed proportion of assets invested in equities and other so-called risky assets. Here, TimePension is compared with two investment-linked life-cycle (target date) products. The focus is especially on the decumulation period, and we show that despite the fact that the life-cycle products reduce investment risk in retirement (compared with TimePension's fixed proportional allocation of assets), the year-over-year stability in benefits provided by TimePension cannot be matched. Even though the overall investment risk on accumulated benefits is at the same level, TimePension provide year-over-year stability, also in case of sharp price changes in the financial market. Our results show that not only investment profiles define the stability of annuity benefits over time. In addition, more fundamental elements of the product design are important. The perspective on product design and development is Danish, but two of the compared products are generic life-cycle products that exist in equivalent forms in many countries. Similarly, the smoothed income annuities could also become an alternative product design in an international perspective.